PREVALENCE AND CORRELATES OF STRESS, ANXIETY AND DEPRESSION AMONG UNDERGRADUATE STUDENTS OF KHYBER MEDICAL UNIVERSITY, PESHAWAR; A CROSSSECTIONAL STUDY - Ali, Zulfiqar; Khalid, Zohaib; Hamza, Muhammad; Darain, Haider; Zeb, Alam; Ul Abidin, Syed Zain (Annals of Allied Health Sciences, 2019)
OBJECTIVES: The aim of this study is to find out prevalence of depression, anxiety and stress. Furthermore, to evaluate potential risk factors that correlates with DAS. METHODS: A cross-sectional study was conducted in KMU, Peshawar. Data was collected from 306 undergraduate students who willingly participated by filling a self-reported symptoms questionnaire which focused on diagnosis of DAS. The data was analysed by SPSS version 22. RESULTS: Out of 306 students, prevalence of depression, anxiety and stress were 199 (65%), 215 (70.3%) and 69.7% respectively. Anxiety was more prevalent in female students while depression and stress were present equally in both genders. Educational (academic performance, post-graduation plans, pressure to succeed) as well as social (relationship with friends and family, homesickness) were significantly related to DAS. Content and time wasted on social media were not associated with DAS according to this study. CONCLUSION: It was observed that the frequency of depression, anxiety and stress among undergraduate students of KMU were high. Significant association was found between DAS and potential educational as well as social risk factor. These findings highlight the need to address mental health problems